Modulation of Carrier‐Induced Defect Kinetics in Multi‐Crystalline Silicon PERC Cells Through Dark Annealing. Issue 2 (6th February 2017) - Chan, Catherine; Fung, Tsun Hang; Abbott, Malcolm; Payne, David; Wenham, Alison; Hallam, Brett; Chen, Ran; Wenham, Stuart
Abstract : In this letter, we report on significant changes caused after dark annealing to the kinetics of the carrier‐induced defect, present in p‐type multi‐crystalline silicon PERC cells. The characteristic shapes of the degradation and regeneration curves under light soaking at 75 °C are dramatically altered, depending on the temperature of an initial dark anneal on the non‐degraded cell. Dark annealing for a fixed time (2.5 h) at temperatures of 200 °C or below, is found to accelerate both the subsequent degradation and regeneration rate and the degradation severity, while at higher temperatures it appears that a possible second defect with a significantly longer degradation and regeneration rate is activated. Through a further increase of the dark annealing temperature, the magnitude of this slow degradation is suppressed. This data provides essential information into the role that thermal history plays in the behavior of the still unidentified defect or defects, which is crucial for future studies of the degradation and methods to mitigate it. Abstract : Low‐temperature dark annealing is shown to have a significant impact on the kinetics of the carrier‐induced defect present in multi‐crystalline silicon passivated emitter and rear cells. Four distinct "modes" of degradation and regeneration behaviour are identified, and the particular mode triggered is dependent on the dark annealing temperature and time. This needs to be considered in any future studies of the still unidentified defect and may help provide insight into its nature.